PERANCANGAN KEMASAN PADA BOARD GAME PETUALANGAN TRADISIONAL RASA - Ramadhan, Yedistya Aulia; Aninditya Daniar; Restu Ismoyo Aji (Pixel :Jurnal Ilmiah Komputer Grafis, 2025)
The packaging design of the Petualangan Tradisional Rasa board game aims to create an educational medium that attracts the interest of young people aged 19–22 toward traditional Indonesian cuisine. This game is designed to address the declining interest among the younger generation in local culinary heritage due to the dominance of modern food culture. The design process employed a combination of qualitative and quantitative methods. The qualitative method involved observation and interviews with Board Game Academy and Table Toys to gather insights on effective board game packaging, while the quantitative method was carried out through questionnaires distributed to the target audience to assess packaging design preferences.